2003
DOI: 10.1111/j.1467-842x.2003.tb00831.x
|View full text |Cite
|
Sign up to set email alerts
|

Domestic violence in South Australia: a population survey of males and females

Abstract: Domestic violence is a serious public health concern often 'hidden' by the lack of appropriate data. This study has shown that domestic violence is frequent and has important social, economic and health consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 36 publications
5
26
3
Order By: Relevance
“…The association between poor labour market affiliation and violent victimization is well known from other studies. 8,12,[19][20][21] However, a previous British case-control study based on unselected ED contacts due to violence did not find any significant relation between unemployment or socioeconomic group and urban violence. 9 The small sample size and the fact that controls were selected among acquaintances of the victims may explain the results.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The association between poor labour market affiliation and violent victimization is well known from other studies. 8,12,[19][20][21] However, a previous British case-control study based on unselected ED contacts due to violence did not find any significant relation between unemployment or socioeconomic group and urban violence. 9 The small sample size and the fact that controls were selected among acquaintances of the victims may explain the results.…”
Section: Discussionmentioning
confidence: 85%
“…[25][26][27] Most other studies have likewise shown that living alone or being single are important risk factors of violent victimization. 7,19,20,25,26,[28][29][30] Low income has been related to an increased likelihood of violent victimization in a few other studies. 20,25 The association between household crowding or family size and violence has also been shown in a few previous studies of domestic violence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors associated with IPV include age, [11][12][13] marital status, 12,13 level of education, [14][15][16][17] presence of children in the household, 11,12 income, 12 and activity limitation (physical/mental disability or health problem). 13,18 Our goal was to assess the prevalence of IPV among recent and nonrecent immigrant women in Canada with a large population-based representative sample.…”
mentioning
confidence: 99%
“…Domestic violence is associated with adverse healthcare outcomes in women (1)(2)(3)(4)(5)(6)(7). It is a common comorbidity in women presenting to healthcare services.…”
Section: Introductionmentioning
confidence: 99%